HUBUNGAN ANTARA EFEKTIVITAS PENGGUNAAN APLIKASI EDUCATION MANAGEMENT INFORMATION SYSTEM (EMIS) DENGAN PENDATAAN PENDIDIKAN DI RAUDHATUL ATHFAL (RA) KABUPATEN SUMEDANG - Fabian Khairah Hisan; Tatang Ibrahim; Wahyu Hidayat (Program Studi Manajemen Pendidikan Islam, 2023)
This study aims to find out how effective the use of the EMIS application is as a data collection system for Raudhatul Athfal (RA) education in Sumedang Regency. The application of the Education Management Information System (EMIS) application has great urgency for institutions, because the data entered determines a policy related to education funds such as School Operational Assistance (BOS) and the Smart Indonesia Program (PIP). The data contained in the EMIS application is also very necessary in making policies and managerial decisions to maintain the quality of education. This research uses a descriptive method with a quantitative approach. The sampling technique combines 2 sampling techniques, namely purposive sampling and simple random sampling of 52 respondents. Data analysis used descriptive statistical analysis and hypothesis testing with one sample t-test (one sample t-test) and assisted with SPSS Version 24. The results showed that the percentage of effectiveness of the EMIS application as an RA data collection system in Sumedang Regency, which was obtained from the respondents' responses, was of 75.25% which is based on the criteria for testing the hypothesis if the value of tcount ≥ ttable (6.04 ≥ 1.675), then Ho is rejected and Ha is accepted.